Giant Filiform Thrombus Anchored at the Outflow of a Percutaneous Aortic Valve Down to the Abdominal Aorta - F, Cianciulli Tomás; E, Estrada Jorge; Eric, Philippe; Denis, Desaulniers; Ze, Zhang; Andrea, Zappi; Robert, Guidoin (Cardiology and Cardiovascular Medicine, 2024)
A 72-year-old patient was fitted with a CoreValve prosthesis and passed away after 132 days. The valve with the 26 cm filiform thrombus attached at the outflow of the valve was harvested at autopsy. A processed porcine pericardium and a CoreValve non-implanted were selected as controls. The porcine pericardium showed a thin layered architecture holding interstitial cells. The collagen bundles showed a sinusoidal morphology in most unloaded collagen tissues. The reference valve consisted of a nitinol frame holding three coapting leaflets. The structure of the pericardium was well preserved; however, the sutures were associated with compression, distortion or damage to the collagen, more frequently on the fibrous side. The floating thrombus was the result of massive thrombosis not only at the outflow of the valve but at the inflow alike. The inflow showed fractured thrombi covering the flow surface. A leaflet was detached at the extraction of the floating thrombus. A second leaflet was rolled up and the third one was still visible. Thrombi were present everywhere and incorporated bacteriemic colonizations. The thrombotic deposits on the remaining leaflet were poorly anchored to its surface; specifically, a fibrous capsule was detached from the leaflet but still fixed to the nitinol frame. Despite major trauma, the sinusoidal structure of the collagen fibers was well preserved. Most of the floating thrombus was reorganized. This lethal issue of percutaneous aortic valve deployment might be more frequent than reported and shall be cautiously investigated, as the risk of thrombotic accumulation cannot be considered as negligible.